A 'Different Class'? Homophily and Heterophily in the Social Class Networks of Britpop. (September 2017) - Millward, Peter; Widdop, Paul; Halpin, Michael
Social network analysis is increasingly recognised as a useful way to explore music scenes. In this article we examine the individuals who were the cultural workforce that comprised the 'Britpop' music scene of the 1990s. The focus of our analysis is homophily and heterophily to determine whether the clusters of friendships and working relationships of those who were 'best connected' in the scene were patterned by original social class position. We find that Britpop's 'whole network' is heterophilic but that its 'sub-networks' are more likely to be social class homophilic. The sub-networks that remain heterophilic are likely to be united by other common experiences that brought individuals in the network to the same social spaces. We suggest that our findings on Britpop might be generalised to the composition of other music scenes, cultural workforces and aggregations of young people. Our study differs from research on, first, British 'indie music' and social class which focuses upon the construction, representation and performance of social location rather than the relationships it might shape and second, the pioneering social network analyses of music scenes which currently lack explicit emphasis on social class.